Student Attendance System Prototype With IoT-Based on Fingerprint and Temperature Sensors in New Normal Era of COVID-19 Pandemic - Simatupang, Joni Welman; Qurais Shihab, Rizky Aryan (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
SourceURL:file:///home/nfrozi/itats/ejurnal/iptek/3000-10559-1-ED.docxCurrently, we are entering the new normal era of the COVID-19 pandemic. Attendance activities can be one of the media for spreading COVID-19. Manual attendance activities make people gather in one place. Manual attendance activities also take a long time. By utilizing internet technology, this research combines body temperature measurement with the internet of things (IoT) based and is equipped with a hand sanitizer. The results of attendance data will be displayed on the web server. This device is made using ESP8266, MLX90164 temperature sensor, fingerprint sensor, IR sensor, pump motor, MB-102 power supply module, and buzzer. The tested device requires only input to activate three sensors (one integrity). As a result, this research succeeded in making the device able to work very well. The device can read body temperature with an average accuracy of 97.55–99.67% with the K3S Infrared Digital Pool Thermometer as a comparison. This device is designed to only take three seconds to clean hands compared to washing hands with soap and running water. The web server design works well too.